Transplantation in Brazil: a SUS’s investment - Santos, Genilde Oliveira dos (Brazilian Journal of Transplantation, 2009)
The Brazilian health policy has been developing since the 20’s upon the creation of the social security system, but only in the 30’s the Instituto de Aposentadoria e Pensão were created (IAPs) organized by professional categories. In the 60’s, Government unified the IAP creating an unique system, (Welfare Department), the INPS (Instituto Nacional de Previdência Social). The SUDS (Sistema Unificado e Descentralizado de Saúde) approved in 1987 was SUS’s (Sistema Unico de saúde) predecessor. One of the health policies now in force is managed by SNT (Sistema Nacional de Transplantes) and the organ transplantation in Brazil is nowadays more than 80% funded by SUS. The present study aims to describe the organ donation process and the organ transplantation as one of the health policies in Brazil. A retrospective descriptive study of the health policies was performed, emphasizing the related organ transplantation procedures; data analyzed was supplied by the Registro Brasileiro de transplantes - RBT and the Central de Captação e Distribuição de Órgãos de Sergipe - CNCDO-SE. Beginning from the RBT data, it was observed the growth in the amount of transplants in the state of Sergipe, the smallest state of the federation, also supported by SUS, which is growing little by little in the amount of transplants, and this can shown through data supplied by CNCDO-SE from 2001 to 2008, particularly in the years of 2001, 2003, 2004 and 2007 in spite of the lack of some resources, as an laboratory of immunogenetic. It was concluded in the research that Brazil is improving its amount of organ donations, according to the RBT registration, with an amount of 3954 transplants of solid organs in 2001, passing to 4836 transplanted in 2007. In 2008, it is noticed a significant reduction of registrations when considering only the 2505 transplants made during the period, and such fact only proves that it is necessary to intensify the organ donation process by applying pertinent discipline comprising the organ donation in universities, orienting the population through the media, lectures in schools aiming to attain an effective decrease on the wait list, since when linking these data to the transplantations performed and the waiting list during that same period, a significant increase is observed on the waiting list each year that belonged to 43 581 people in 2001, passing to 68 908 in 2008.